Folfiri-Aflibercept vs. Folfiri-Bevacizumab as Second Line Treatment of RAS Mutated Metastatic Colorectal Cancer in Real Practice - Ottaiano, Alessandro; Capozzi, Monica; Tafuto, Salvatore; De Stefano, Alfonso; De Divitiis, Chiara; Romano, Carmela; Avallone, Antonio; Nasti, Guglielmo (Frontiers in Oncology, 2019)
Background. There are no clinical studies comparing the efficacy of bevacizumab vs aflibercept in association with folfiri in RAS mutated (RAS-M) metastatic colorectal cancer patients (mCRC) pretreated with folfox and bevacizumab. Patients and methods. Consecutive RAS-M unresectable mCRC patients progressing to first-line folfox/bevacizumab were treated with 12 cycles of folfiri/bevacizumab (arm A) or folfiri/aflibercept (arm B) at Oncologist discretion. Differences in overall survival between the two schedules were analyzed. Responses and toxicities were described with RECIST and NCI-CTC v4.0, respectively. Results. Seventy-four patients were treated from January 2014 to January 2018; 31 with arm A, 43 with arm B. Among clinical factors there was a predominance of more extended disease (>two metastatic sites) in arm B (26/43 [60.5%] vs 10/31 [32.2%] arm A; p=0.0414). Fifty-nine patients were evaluable for response: arm A, 5 PR (Partial Response), 15 SD (Stable Disease), 8 PD (Progressive Disease); arm B, 5 PR, 16 SD, 10 PD. There were no grade 4 toxic events. Duration of first-line chemotherapy was significantly shorter in patients treated in arm B (12 pts <6 months, 16 pts ≥6 and <12, 15 pts ≥12) vs arm A (1 pts <6 months, 14 pts ≥6 and <12, 16 pts ≥12) (p=0.0210); these patients were excluded from survival analysis to avoid prognostic interferences. No maintenance treatment with aflibercept was done in arm B while in arm A bevacizumab with or without fluorouracil and folinic acid were allowed. Median OS were 8.9 months in arm A vs 12.1 months in arm B (+3.2 months; p=0.9331, HR: 1.02; 95% CI: 0.57-1.84). Six-months survivals were 65% in arm A and 80% in arm B. Conclusions. Folfiri/bevacizumab and folfiri/aflibercept are equally effective second-line therapies in RAS-M mCRC patients. Although not significant, folfiri/aflibercept was associated with a lower risk of death particularly during the 6-months induction phase.